HUBUNGAN POLA ASUH ORANG TUA DENGAN MINAT BELAJAR SISWA SEKOLAH DASAR MUHAMMADIYAH JOGOKARIYAN YOGYAKARTA - Chalin Kurniawati Apritia; Sutari Imam Barnadib (KELUARGA: Jurnal Ilmiah Pendidikan Kesejahteraan Keluarga, 2015)
The purpose of researchÂ  is to (1) describe parenting, (2) describe be students learning interest, and (3) The relationship between parenting and student learning interest in elementary school Muhammadiyah Jogokariyan Yogyakarta. This research method using a closed interview and documentation. The results of research showed that mojority of student parents in elementary school Muhammadiyah Jogokariyan Yogyakarta have enough parenting with categories on frequency 48 with relative frequency 67,6% and learning interest have enough categories on frequency 45 with relative frequency 63,4%. Â Based on the results of hypothesis test that using Product Moment correlation, the correlation coefficient values r account to 0.537. To significant test value should be consulted in the values table rÏ‡y. R table value with value N = 71 at 5% significance level was 0.227. So, r accont values be above obtained r table values 0.537> 0.227. The meaning, there is a relations between parenting with learning interest a students in elementary school Muhammadiyah Jogokariyan Yogyakarta.Â